Designing great data products - Howard, Jeremy; Zwemer, Margit; Loukides, Michael Kosta (O'Reilly Media, 2012)
Annotation
Online resource; title from title screen (Safari, viewed Oct. 4, 2012)
Keywords: Programming (Mathematics); Online algorithms; Business forecasting; Programmation (Mathématiques); Algorithmes en ligne; Prévision commerciale